The Mediterranean Sea as a border: difficulties surrounding the concept of migration. - Fajardo Fernández, Rocío; Soriano Miras, Rosa María (Centro de Estudios de las Migraciones y las Relaciones Interculturales, 2017)
The main purpose of the present article is to face some difficulties that arise from researching the so called “irregular migration”. Focusing on the southern border of Europe and the Mediterranean Sea, we capture some troubles and reflections based on other research projects carried out by ourselves and by others. We previously did some conceptual work based on the ideas of migration and border and how these are related to other categories, such as citizenship. Here, we make an exercise of reflection into the sociological field. To this end, we utilise some theoretical tools such as deconstruction, bibliographic review and conceptual analysis. We show and compare several concepts and definitions of the theoretical subject, taking into account its empirical counterpart. We analyse different ways of understanding migration and its dimensions, delving deeper into their weaknesses and strengths. Due to the importance of borders in the study of migration, their dimensions are analysed too. We point out some structural contradictions in borders, both empirical and discursive. We conclude that the best way to refer to our object of study is talking about candidates to migration because there is a selection made through a process of bordering. As social researchers, we are presented with the challenge to build the right analytical categories in order to control their performativity, and this category is the one that we think better fits our object among those we have analysed. Also, it has some inertia beyond our work. Contradictions also arise when trying to define the different situations that people who (try to) migrate come across, but we do so with the aim of highlighting the extreme situations that are reproduced systematically, as part of a wider structure
El Mediterráneo como frontera: dificultades que envuelven al concepto de migración.
Keywords: Emigración e inmigración - Mediterráneo; Migration border; Mediterranean sea; Epistemology; Irregularity